2009
DOI: 10.1038/sj.bjc.6605175
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 18 in plasma of patients with gastrointestinal adenocarcinoma as a biomarker of tumour response

Abstract: BACKGROUND: Plasma biomarkers may be particularly useful as a predictor or early marker of clinical response to treatment in addition to radiological imaging. Cytokeratin 18 (CK18) is an epithelial-specific cytokeratin that undergoes cleavage by caspases during apoptosis. Measurement of caspase-cleaved (CK18 -Asp396) or total cytokeratin 18 (CK18) from epithelial-derived tumours could be a simple, non-invasive way to monitor or predict responses to treatment. METHODS: Soluble plasma CK18 -Asp396 and CK18 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 33 publications
4
55
0
Order By: Relevance
“…Studies on specific tumour types include lung (Ulukaya et al, 2007;Hou et al, 2009), breast (Olofsson et al, 2007, prostate (Kramer et al, 2006), head and neck (Ozturk et al, 2009), colorectal (Ausch et al, 2009Koelink et al, 2009) and testicular (de Haas et al, 2008) tumours. Although a recent study concluded that plasma levels of CK18 are a potential marker of tumour response in patients with advanced gastrointestinal malignancy (Scott et al, 2009) no previous studies have been reported in patients with pancreatic cancer.The objective of this study was to characterise the baseline levels of circulating plasma CK18 concentrations using both the M65 and M30 ELISA assays in patients with pancreatic cancer. Correlations were also examined between CK18 and the circulating levels of carbohydrate antigen 19-9 (CA19-9), the only widely used biomarker in pancreatic cancer (Smith et al, 2008).…”
mentioning
confidence: 98%
“…Studies on specific tumour types include lung (Ulukaya et al, 2007;Hou et al, 2009), breast (Olofsson et al, 2007, prostate (Kramer et al, 2006), head and neck (Ozturk et al, 2009), colorectal (Ausch et al, 2009Koelink et al, 2009) and testicular (de Haas et al, 2008) tumours. Although a recent study concluded that plasma levels of CK18 are a potential marker of tumour response in patients with advanced gastrointestinal malignancy (Scott et al, 2009) no previous studies have been reported in patients with pancreatic cancer.The objective of this study was to characterise the baseline levels of circulating plasma CK18 concentrations using both the M65 and M30 ELISA assays in patients with pancreatic cancer. Correlations were also examined between CK18 and the circulating levels of carbohydrate antigen 19-9 (CA19-9), the only widely used biomarker in pancreatic cancer (Smith et al, 2008).…”
mentioning
confidence: 98%
“…and M65 levels were also increased in patients with advanced gastrointestinal adenocarcinoma [2,25]. Yaman E et al reported that serum M30 and M65 levels were increased in patients with advanced gastric cancer, and only M30 levels reflected the tumor load [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, M65 and M30 levels reflect chemotherapy-induced changes in testicular germ cell cancer [21]. CK18 levels before initiation of chemotherapy may be 17 an indicator of tumor response to the chemotherapy in patients with advanced gastrointestinal adenocarcinomas [2]. On the other hand, the levels of M30 were increased during chemotherapy in patients with gastrointestinal cancer, which was also related with response to the therapy [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations